ECO-CENTRIC RURAL REVIVAL: FACTORS FOR ECOLOGICAL LIVABILITY IN HANGZHOU - Yang, Xin; Chen, Xue; Sun , Xiaojie (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
China's rapid economic growth and urbanization have presented a dual challenge of rural decay and ecological degradation. This paper explores the interplay between rural revitalization and ecological livability in the context of Hangzhou, shedding light on crucial factors influencing the construction of ecological livability in peri-urban areas. As China strives to balance economic development with environmental sustainability, understanding these factors becomes imperative.